The role of maritime container terminals in the provision of logistics services - Bartosiewicz, Aleksandra (Management and Administration Journal, 2023)
A modern maritime container terminal must provide services within its area or in the nearby logistics centers. What is more,so as to adjust to changing market conditions marine terminals have to provide service packages for cargos (retail and distribution, handling, transportation and transshipment), vessels (supply, repair, towing, mooring or industrial and other auxiliary services) and a crew (social, health, hotel or information services). Since ports are forced to widen the range of their services to stay competitive in the global economy, in the article the role of maritime container terminals will be described in the provision of logistics services.